Diktaturen in Lateinamerika im Zeitalter des kalten Krieges - Cwik, Christian; König, Hans-Joachim; Rinke, Stefan (Historamericana, 2022)
The volume presents new research on the history of dictatorships in Latin America between 1945 and 1990. The presentation of differently oriented dictatorships in Cuba, Venezuela, Peru, Panama, Argentina and Chile creates a differentiated picture of the emergence and foundation of dictatorships in this region.